THE INFLUENCE OF THE RATIO AND GRAIN SIZE OF THE NATURAL MINERAL SIO2 ON THE STRENGTH OF CaCO3 MIXED CONCRETE - Joni, Idon; Ariyanto, Sandy Vikki (PHYDAGOGIC : Jurnal Fisika dan Pembelajarannya, 2024)
In 2020, a research team conducted XRD analysis of the sand from Mandangin Island, Sampang Regency. The results showed that the sand contained a CaCO3 phase of over 90%, while the XRF analysis revealed that 94% of the minerals in the sand were Ca. Two years later, in 2022, the same team conducted a compression test on concrete mixed with CaCO3 sand, and the highest value they obtained was 22.68 MPa. However, they found that further research is needed to optimize the use of CaCO3, rice husks, and cement in concrete production and to maximize the potential of this natural material. To achieve this, they ground the rice husks to a fine powder and filtered them using a 200 mesh and 300 mesh sieve, while also varying the mixture ratios of rice husks : CaCO3 sand : and cement. The XRF results of the mineral content of rice husk ash showed that it contained 84% Si. In terms of compressive strength, the highest value of 27.2 MPa was achieved by using a ratio of 0.5:1:1.5 for rice husk ash, sand, and cement, respectively. The team also found that the smaller the filter used, the higher the compressive strength test results, with the 300 mesh filter producing the highest value of 13.6 MPa.